2020
DOI: 10.1021/acsami.9b21490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Proximity to Supporting Substrate on van der Waals Epitaxy of Atomically Thin Graphene/Hexagonal Boron Nitride Heterostructures

Abstract: Combining graphene and the insulating hexagonal boron nitride (h-BN) into two-dimensional heterostructures is promising for novel, atomically thin electronic nanodevices. A heteroepitaxial growth, in which these materials are grown on top of each other, will be crucial for their scalable device integration. However, during this so-called van der Waals epitaxy, not only the atomically thin substrate itself must be considered but also the influences from the supporting substrate below it. Here, we report not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Another complication is added when h‐BN is combined with graphene in vdW heterostructures: The h‐BN E 2g phonon mode might interfere with the relatively broad defect‐related D peak of graphene appearing in the same spectral regions for visible excitation. [ 20,21 ] A similar problem is found for heterostructures formed of h‐BN and epitaxial graphene on SiC(0001), where even in the absence of a D peak, the h‐BN signal can superimpose with the Raman signal originating from the 6(√3 × √3) R 30° interfacial layer between graphene and SiC (also known as buffer layer), [ 18 ] which consists of broad bands spreading over 1200 and 1660 cm −1 . [ 23 ]…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Another complication is added when h‐BN is combined with graphene in vdW heterostructures: The h‐BN E 2g phonon mode might interfere with the relatively broad defect‐related D peak of graphene appearing in the same spectral regions for visible excitation. [ 20,21 ] A similar problem is found for heterostructures formed of h‐BN and epitaxial graphene on SiC(0001), where even in the absence of a D peak, the h‐BN signal can superimpose with the Raman signal originating from the 6(√3 × √3) R 30° interfacial layer between graphene and SiC (also known as buffer layer), [ 18 ] which consists of broad bands spreading over 1200 and 1660 cm −1 . [ 23 ]…”
Section: Introductionmentioning
confidence: 77%
“…For their preparation, various methods have been employed, the most common still being mechanical exfoliation of micrometer-sized flakes from bulk h-BN crystals. [12,13] Nevertheless, aiming at the realization of large-area synthesis-a crucial step towards applications-scalable approaches such as chemical vapor deposition (CVD), [14] metalorganic vapor phase epitaxy, [15] atomic layer deposition, [16] and molecular beam epitaxy (MBE) [10,[17][18][19][20][21] have been explored as well. Here, it is particularly important to be able to evaluate the quality of the synthesized films regarding their structure and optoelectronic properties and compare it, for instance, with results achieved for state-of-the-art bulk h-BN crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49] In addition to CVD technology, magnetron sputtering and MBE can also enable the growth of h-BN on graphene. [50][51][52] High-quality multilayer h-BN films with controllable layers on Ru(0001) or Gr/Ru(0001) substrates have been generated by the magnetron sputtering of B in N 2 /Ar (Figure 3b,c). [50] Interestingly, direct growth on Ru(0001) produces h-NB with A-A′-A stacking, whereas the termination of the Ru surface with ML graphene preferentially forms h-BN with A-B-C stacking (r-BN) (Figure 3d).…”
Section: Stacking Order and Interfacial Propertiesmentioning
confidence: 99%
“…[ 50 ] r‐BN provides a more facile, diffusionless pathway for the transformation to cubic BN. Heilmann et al [ 51 ] demonstrated the strong influence of the number of graphene layers on the vdW epitaxial growth of h‐BN by MBE. The additional layer in bilayer graphene enhances the distance to the corrugated, carbon‐rich interface of the supporting SiC substrate and thus diminishes its influence on the vdW epitaxy, contributing to the homogeneous formation of h‐BN and thereby forming atomically smooth heterostructures (Figure 3e).…”
Section: Controllable Synthesis Of 2d Vdwhs and Vdwslsmentioning
confidence: 99%